Psychological well-being of rural left-behind women in Northwest China and its associated factors: a regional, population-based study - Niu, Fang; Wang, Xiang (Frontiers in Public Health, 2024)
PurposeGrowing awareness has highlighted the challenging living condition faced by rural left-behind women (RLW), yet their psychological well-being has not been fully investigated. This study aims to investigate the psychological well-being of RLW in Northwest China and exploring its associated factors.Samples and methodsA total of 697 RLW from five provincial regions were enrolled. Sociodemographic characteristics were collected using a set of researcher-designed questionnaires. Depression, anxiety, and feeling of security were assessed using the Zung’s self-rating depression scale (SDS), Zung’s self-rating anxiety scale (SAS), and security questionnaire (SQ), respectively.ResultsThe prevalences of depression and anxiety among RLW were 35.7 and 37.6%, respectively, and feelings of security was relatively low in RLW, with a mean SQ score of 50.16 ± 11.37. Chi-square tests and multiple linear regression analyses indicated that labor intensity, physical health conditions, marital satisfaction and stability, relationships with children, frequency of husband coming home, left-behind duration, domestic violence, and sexual harassment after husbands left were risk factors of psychological well-being of RLW.ConclusionThese findings revealed that the psychological well-being of RLW in Northwest China is not promising, which should therefore, be given special attention. It is essential to prioritize the improvement of the psychological well-being for RLW by providing accessible and targeted supports and interventions tailored to cope with their challenges.